Simplifying Cosplay Costume Selection with a Web-Based Recommendation System using Simple Additive Weighting Method - Timothy Gracie Hasudungan Wijaya; Wirawan Istiono (Universitas Islam Raden Rahmat, Malang, 2024)
Cosplay is an activity where individuals imitate the dressing style of a character, typically from fictional works such as games, anime, VTubers, and others. Before engaging in cosplay activities, cosplayers need to choose the desired costume according to their individual needs. Therefore, cosplayers often experience confusion in selecting a cosplay costume due to the many costume options and the desired costume criteria. One way to assist in making decisions is through a recommendation system. A recommendation system can help users make decisions based on their preferences. In this study, the design and development of a webbased recommendation system for selecting cosplay costumes using the Simple Additive Weighting method were conducted. This system was then evaluated by 52 respondents. Based on a survey conducted using the EUCS method to measure user satisfaction levels, an average score of 80.65% was obtained.